Jellyfish Peptide as an Alternative Source of Antioxidant - Lichao Teng; Xueqin Wang; Huahua Yu; Rongfeng Li; Hao Geng; Ronge Xing; Song Liu; Pengcheng Li (MDPI AG, 2023)
Jellyfish is a valuable biological resource in marine ecosystems, and blooms been observed in numerous coastal regions. However, their utility is limited by their high water content. Recent research has focused on extracting antioxidants from marine sources. In this study, we obtained jellyfish peptides (JPHT-2) through enzymatic hydrolysis of lyophilized jellyfish powder under optimal conditions and measured their antioxidant activity. Our findings indicate that JPHT-2 possesses significant radical-scavenging activity and reducing power. At a concentration of 0.74 mg/mL, JPHT-2 exhibited a remarkable ability to scavenge hydroxyl radicals, with a rate of up to 50%. The EC50 values for scavenging superoxide anion and DPPH radical were 1.55 mg/mL and 1.99 mg/mL, respectively. At the cellular level, JPHT-2 was able to protect HaCaT cells from H2O2-induced oxidative damage by increasing the level of superoxide dismutase (SOD) in cells. In conclusion, jellyfish peptides with low molecular weight can be easily obtained through hydrolysis with three enzymes and exhibit excellent antioxidant activity and safety. Jellyfish can serve as a promising source of antioxidants.